Updated Bibliography of Alexander Altmann's Published Writings - Altman, Manfred (AJS review, 1994)
Alexander Altmann passed away six years ago, yet his presence is still very much felt by all who work in the field of medieval and early modern Jewish philosophy and mysticism. The recent publication of his early essays on Jewish theology and the crisis of German Jewry in the thirties will bring him to the attention of a still wider circle of readers. His place among the foremost scholars of Judaic studies in our century is assured.